Bacterial enzyme mediated biosynthesis of gold nanoparticles - Bharde, Atul A.; Kulkarni, Aarohi; Rao, Mala; Prabhune, Asmita; Sastry, Murali (Journal of Nanoscience and Nanotechnology, 2007)
Development of synthesis methods for anisotropic metal nanoparticles is of considerable interest due to their remarkable optoelectronic properties. Various shapes ranging from rods to cubes to tetrapods and prisms may be obtained by chemical methods. Here we show that anisotropic gold nanoparticles can be synthesized biologically by the bacterium Actinobacter spp. when challenged with gold chloride in the presence of Bovine serum albumin (BSA). We also observed that synthesis of gold nanoparticles occur with simultaneous induction of the protease enzyme secreted by the bacterium in the presence of BSA. The presence of BSA helps to enhance the rate of gold nanoparticles biosynthesis and may also impart some shape control. Controlling simple experimental conditions like incubation temperature and presence or absence of oxygen have drastic effect on the reaction rate and the morphology of the particles. Various assay experiments show that the presence of enzyme protease can act as a reducing as well as shape directing agent.
Keywords: Biosynthesis; bovine serum; gold nanoparticles

Biochemical characterization of an aspartic protease from vigna radiata: kinetic interactions with the classical inhibitor pepstatin implicating a tight binding mechanism - Kulkarni, Aarohi; Rao, Mala (Biochimica Et Biophysica Acta-Proteins and Proteomics, 2007)
{Aspartic proteases are the focus of recent research interest in understanding the physiological importance of this class of enzymes in plants. This is the first report of an aspartic protease from the seeds of Vigna radiata. The aspartic protease was purified to homogeneity by fractional ammonium sulfate precipitation and pepstatin-A agarose affinity column. It was found to have a molecular weight of 67,406 Da by gel filtration chromatography. SDS-PAGE analysis revealed the presence of a heterodimer with subunits of molecular weights of 44,024 and 23,349 Da respectively. The enzyme was pH stable with the amino acid analysis confirming the molecular weight of the protein. The substrate cleavage site as analyzed by using the synthetic substrate was found to be the Phe-Tyr bond. The kinetic interactions of the enzyme were studied with the universal inhibitor, pepstatin A. This is the first report on the interactions of a plant aspartic protease with pepstatin-A, an inhibitor from a microbial source. A competitive one-step mechanism of binding is observed. The progress curves are time-dependent and consistent with tight binding inhibition. The K(i) value of the reversible complex of pepstatin with the enzyme was 0.87 mu M whereas the overall inhibition constant K(i)*
Keywords: ant colony; global optimization; metaheuristics; multimodal continuous functions; particle swarm optimization